2023
DOI: 10.1161/strokeaha.123.043160
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in the Risk of Ischemic Stroke After Nontraumatic Intracerebral Hemorrhage

Abstract: BACKGROUND: Intracerebral hemorrhage (ICH) is associated with an increased risk of ischemic stroke. Whether there are racial and ethnic disparities in the risk of ischemic stroke after ICH is poorly understood. We therefore aimed to test the hypothesis that non-Hispanic Black and Hispanic ICH patients have a higher risk of ischemic stroke compared with non-Hispanic White ICH patients. METHODS: We performed a retrospective cohort study usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Several recent studies have shown a link between ICH and the subsequent risk of MACCE. [1][2][3][4] This increased risk of MACCE is influenced by demographic factors, mainly race and ethnicity, 7 and ICH-related factors, particularly hematoma location. 8,9 However, since prior studies mainly examined large population cohorts, they lacked important ICH characteristics such as admission hematoma volume and the presence of IVH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have shown a link between ICH and the subsequent risk of MACCE. [1][2][3][4] This increased risk of MACCE is influenced by demographic factors, mainly race and ethnicity, 7 and ICH-related factors, particularly hematoma location. 8,9 However, since prior studies mainly examined large population cohorts, they lacked important ICH characteristics such as admission hematoma volume and the presence of IVH.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that Black patients with ICH and those of Hispanic ethnicity have a higher ischemic stroke risk compared with White patients with ICH. 7 Furthermore, hematoma location may play a role in the fact that the risk of MACCE is higher after a lobar ICH, mainly due to a heightened risk of recurrent ICH, while there appears to be a trend toward more ischemic events among patients with a deep ICH. 5,8,9 It is, however, unknown whether other hematoma characteristics, such as hematoma volume, are also associated with ischemic stroke risk.…”
mentioning
confidence: 99%
“…4,5 Multiple studies have demonstrated higher incidences of ischemic and hemorrhagic strokes among minority racial and ethnic groups, especially non-Hispanic Black and Hispanic patients. [6][7][8] Moreover, patient access to health care differs among racial and ethnic groups, with White patients being more likely to use medical services compared with Black, Asian, and Hispanic patients. 9,10 This becomes important since the time and quality of treatment significantly impact survival rates and functional long-term recovery.…”
mentioning
confidence: 99%